Penerapan Sanksi Pidana Perda Pajak dan Retribusi Bidang Pendapatan di Kota Ternate - Malik, Faissal; Abdulajid, Syawal (Jurnal Komunikasi Hukum, 2021)
The application of regional regulations in the field of RegionalÂ Taxes and Retribution in Ternate City has not yet been submitted to the Court with criminal convictions, but it is realized that the regional regulation enforcement officers have not fulfilled the tax obligations. Even so, violations of the Tax and Retribution Regional Regulations on administrative law sanctions are chosen to be enforced rather than criminal sanctions because administrative legal sanctions are more effective in their enforcement. Therefore, the formation of regional regulations on taxes and levies does not only pay attention to aspects of legal substance, but also aspects of structure and cultural aspects, in the form of the availability of regional law enforcement officers which in turn result in enforcement of regional regulations on taxes and levies so that criminal sanctions can be utilized to increase original income. Regional (PAD).